Learning in Online Continuing Professional Development: An Institutionalist View on the Personal Learning Environment - Mark William Johnson; Denise Prescott; Sarah Lyon (Springer, 2017)
The nature of institutions is an important question for the Personal Learning Environment (PLE). Whilst the PLE has tended to focus on what is considered to be "non-institutional" technology like social software, most online tools today have a corporate/institutional foundation. How should educators position themselves with learners who have to negotiate different institutional and discursive contexts - whether within corporate social software, formal education, work or the family? Drawing on previous work focusing on how learners maintain personal coherence in organising learning between different contexts, institutional theory is used to revise the model of the learner as a 'viable system', which focuses on the dynamics of transactions that learners make with different institutional entities. Data from an online Continuing Professional Development (CPD) course in acute cancer care is analysed to show how learner transactions indicate constraints bearing upon learners both from their professional context and from their formal educational study. The pattern of learner engagement suggests that the interaction of constraints creates the conditions to motivate in-depth contribution to the course forums.  This finding leads us to suggest a rethink of pedagogy within the PLE, and a broader consideration of institutional and other constraints in educational dynamics.